2012
DOI: 10.1155/2012/270670
|View full text |Cite
|
Sign up to set email alerts
|

Possible Roles of Proinflammatory and Chemoattractive Cytokines Produced by Human Fetal Membrane Cells in the Pathology of Adverse Pregnancy Outcomes Associated with Influenza Virus Infection

Abstract: Pregnant women are at an increased risk of influenza-associated adverse outcomes, such as premature delivery, based on data from the latest pandemic with a novel influenza A (H1N1) virus in 2009-2010. It has been suggested that the transplacental transmission of influenza viruses is rarely detected in humans. A series of our study has demonstrated that influenza virus infection induced apoptosis in primary cultured human fetal membrane chorion cells, from which a factor with monocyte differentiation-inducing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 218 publications
(280 reference statements)
1
43
1
Order By: Relevance
“…Abortions in influenza A virus (IAV)-infected humans as well as animals, including pigs, seem to be a result of high fever and a ''cytokine storm'' associated with acute infection, but transplacental transmission of the virus has been also reported [5][6][7][8][9][10]. Influenza virus has also been isolated from amnion and chorion tissues in guinea pigs [11] and amniotic fluid in ferrets [12]. To date, there is insufficient data to conclude that IAV has a specific and direct association with the occurrence of reproductive problems.…”
Section: Introductionmentioning
confidence: 99%
“…Abortions in influenza A virus (IAV)-infected humans as well as animals, including pigs, seem to be a result of high fever and a ''cytokine storm'' associated with acute infection, but transplacental transmission of the virus has been also reported [5][6][7][8][9][10]. Influenza virus has also been isolated from amnion and chorion tissues in guinea pigs [11] and amniotic fluid in ferrets [12]. To date, there is insufficient data to conclude that IAV has a specific and direct association with the occurrence of reproductive problems.…”
Section: Introductionmentioning
confidence: 99%
“…2,11 The adverse fetal effects of influenza infection during pregnancy could be due to a direct biological effect of maternal viral infection in the fetus, or secondary to influenza illness stimulating an inflammatory response which could include an increase in prostaglandin E and other cytokine and chemokine production that could precipitate labor. 12 On the same note influenza infection normally presents with fever and it has been shown that hyperthermia during pregnancy is associated with an increased risk for certain birth defects and birth adverse outcomes. 13 Congenital transmission of influenza virus from mother to fetus in utero has been reported to be an infrequent phenomenon.…”
Section: Impact Of Influenza Disease On Pregnancy Outcomesmentioning
confidence: 99%
“…The state of relative immunosuppression during pregnancy and early life may contribute to increased susceptibility to infectious diseases and not surprisingly, pregnant women and newborns have been shown to be at increased risk of influenza complications including hospitalization, intensive care unit admission and death. [1][2][3][4] A US study showed that of pregnant women hospitalized with pandemic H1N1/2009 pdm infection, 22.6% required admission to intensive care units. 3 Similarly, during previous influenza pandemics in 1918/1919 and 1957/1958 mortality rates were considerably higher among pregnant women than in the general population, in addition to a high rate of pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%